2019
DOI: 10.1016/j.rmed.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect economic and health consequences related to sarcoidosis in Denmark: A national register-based study

Abstract: Background: Sarcoidosis is a systemic disease that primarily affects the younger population. Longitudinal studies of the economic burden of sarcoidosis are scarce. This study evaluates overall the economic burden of sarcoidosis in Denmark before and after initial diagnosis. Methods: We identified patients with sarcoidosis in the Danish National Patient Registry (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010). All controls were randomly selected and matched concerning age, gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Long-lasting preclinical sarcoidosis was described in several other studies. Comparing sick leave absence, earnings, and health expenses as indicators of general health status between sarcoidosis and nonsarcoidosis comparators, large studies from Sweden [3] and Denmark [6] indicate that preclinical disease might last for at least a year. Using employer health insurance data from the United States, an investigation found more outpatient visits during the year before diagnosis in sarcoidosis compared to other pulmonary diseases [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-lasting preclinical sarcoidosis was described in several other studies. Comparing sick leave absence, earnings, and health expenses as indicators of general health status between sarcoidosis and nonsarcoidosis comparators, large studies from Sweden [3] and Denmark [6] indicate that preclinical disease might last for at least a year. Using employer health insurance data from the United States, an investigation found more outpatient visits during the year before diagnosis in sarcoidosis compared to other pulmonary diseases [5].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcoidosis, a granulomatous disease of unknown etiology, may present in multiple forms and affect several organs [1,2]. As a result and in the absence of a pathognomonic test, diagnosis is often a long and complex process involving invasive examinations and exclusion of alternative diagnoses [2][3][4][5][6]. According to international and Swedish recommendations, pharmacologic treatment, initially systemic corticosteroids that are replaced thereafter by steroid-sparing agents, is reserved for patients with debilitating symptoms or progressive disease [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients with sarcoidosis were less likely to be employed and more likely to be receiving unemployment and social benefits beginning 5 years prior to diagnosis and extending up to 9 years after diagnosis [81]. Patients aged 40–64 years had the lowest income from employment (relative to controls) [81]. Data from the United States presents similar findings [40 ▪▪ ,84].…”
Section: Diversity and Disparity In The Treatment Clinical Course And...mentioning
confidence: 78%
“…Sikjaer et al [81] found that the total health expenses for patients with sarcoidosis was significantly higher than for population-based controls beginning 11 years before and extending up to 11 years after diagnosis. Furthermore, patients with sarcoidosis were less likely to be employed and more likely to be receiving unemployment and social benefits beginning 5 years prior to diagnosis and extending up to 9 years after diagnosis [81]. Patients aged 40-64 years had the lowest income from employment (relative to controls) [81].…”
Section: Disparities In the Overall Financial Burden Of Sarcoidosismentioning
confidence: 99%
“…Most evidence corresponding to the economic burden of ILDs is however restricted to distinct service providers (e.g. hospital costs) [ 16 ], focused on pre-selected ILD subtypes [ 17 , 18 ] or took a cross-sectional perspective on costs of care [ 14 ]. A comprehensive assessment on costs associated with drug treatment that accounts for potentially different trends in various ILDs is lacking so far.…”
Section: Introductionmentioning
confidence: 99%